Comparative Analysis Of Service Quality On Patient Satisfaction Levels In Government And Private Hospitals In Medan City In 2022 - Bebie Ayura; Sri Wahyuni Nasution; Rapael Ginting (CV. Inara, 2024)
This study compares service quality to patient satisfaction in government and private hospitals in Medan City in 2022. This study used a survey method using a questionnaire as a data collection instrument. The research respondents were patients who used government and private hospital services. The data collected includes service quality dimensions, such as tangibles, reliability, responsiveness, assurance, and empathy. In addition, the data also consists of the level of patient satisfaction with the services provided by the hospital. Comparative analysis of service quality and patient satisfaction levels was carried out using appropriate statistical techniques, such as testing the difference between two groups of hospitals (government vs. private) using appropriate statistical tests. The results of this analysis will provide an understanding of the differences in service quality between government and private hospitals, as well as the related level of patient satisfaction. This research is expected to contribute to the development and improvement of health services in hospitals, especially in the city of Medan. The results of this study can also be input for hospital management to improve service quality and patient satisfaction. Thus, hospitals can provide better services and meet patient expectations to enhance the reputation and competitiveness of both government and private hospitals in Medan City. Especially in the city of Medan. The results of this study can also be input for hospital management to improve service quality and patient satisfaction. Thus, hospitals can provide better services and meet patient expectations to enhance the reputation and competitiveness of both government and private hospitals in Medan City. Especially in the city of Medan. The results of this study can also be input for hospital management to improve service quality and patient satisfaction. Thus, hospitals can provide better services and meet patient expectations to enhance the reputation and competitiveness of both government and private hospitals in Medan City.